Kool Kids Pre-School / Muhammad Nur Ikhwan Rosmin ... [et al.] - Rosmin, Muhammad Nur Ikhwan; Sabar, Sabarinani; Rospi, Nur Syamih; Abdul Razak, Nurul Azra; Medar, Izzah Nur Syakirah (2015)
The business called Kool Kids Pre-School where it is providing a service for children at the age of 4 - 6 years old to take care of and educate them. This company is partnership with 5 members which are Muhammad Nur lkhwan Bin Rosmin, Nurul Azra Binti Abdul Razak, Izz.ah Nur Syakirah Binti Medar, Nur Syamih Binti Rospi and Sabarinani Binti Sabar. The location is at Alamesra where the target market is for parents who have children and need somebody to take care of. This is to accommodate children while educating them of basic literacy, problem solving, programming, and practical 'ibadah' for Muslims. Each of the partners has contributed RM 20,000 and RM 48,077 of loan for supporting the business to be running for the long term.